IMPLIKASI MANAGERIAL JUDGMENT TERHADAP PENGIMPLEMENTASIAN IFRS : (Studi Konseptual) - Catharina Cantik Batika (AKUNTANSI 45, 2023)
This article is prepared to understand the implications of managerial judgment as a result of this IFRS convergence.The convergence of International Financial Reporting Standards (IFRS) in Indonesia is continuously implemented by DSAK IAI. This is done to achieve harmonization between IFRS and PSAK. One aspect to consider regarding the adoption of IFRS in relation to PSAK is the reduction in the number of accounting methods that can be chosen, which can minimize accounting fraud. Another important consideration is the significant managerial judgment required in the process of financial reporting when implementing IFRS. If managers have self-interest, the magnitude of this managerial judgment can be used as a basis for earnings management.